2008
DOI: 10.1111/j.1525-142x.2008.00243.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity in insects: the effects of substrate color on the coloration of two ground‐hopper species

Abstract: The question of how phenotypic variation is maintained within populations has long been a central issue in evolutionary biology. Most of these studies focused on the maintenance of genetic variability, but the phenotype of organisms may also be influenced by environmental cues experienced during ontogeny. Color polymorphism has received particular attention in evolutionary studies as it has strong fitness consequences. However, if body coloration is influenced by the environment, any conclusions on evolutionar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
2
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 55 publications
2
43
2
4
Order By: Relevance
“…Our results and conclusions are incongruent, however, with those of Hochkirch et al (2008). These authors reared T. subulata and Tetrix ceperoi (Bolívar, 1887) on different visual backgrounds using a split-brood design but concluded that whereas the pattern itself was not influenced by plasticity, basic color showed a plastic response to the color of the rearing substrate experienced during growth, with individuals exposed to darker backgrounds developing darker color patterns.…”
Section: Discussioncontrasting
confidence: 53%
See 4 more Smart Citations
“…Our results and conclusions are incongruent, however, with those of Hochkirch et al (2008). These authors reared T. subulata and Tetrix ceperoi (Bolívar, 1887) on different visual backgrounds using a split-brood design but concluded that whereas the pattern itself was not influenced by plasticity, basic color showed a plastic response to the color of the rearing substrate experienced during growth, with individuals exposed to darker backgrounds developing darker color patterns.…”
Section: Discussioncontrasting
confidence: 53%
“…These authors reared T. subulata and Tetrix ceperoi (Bolívar, 1887) on different visual backgrounds using a split-brood design but concluded that whereas the pattern itself was not influenced by plasticity, basic color showed a plastic response to the color of the rearing substrate experienced during growth, with individuals exposed to darker backgrounds developing darker color patterns. What may account for the discrepancy between our results and those of Hochkirch et al (2008)? First, there may be a biological explanation for the different findings.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations